Pengembangan E-Modul Berbasis Kontekstual Pada Materi Bangun Datar Segi Empat untuk Kelas VII - Satiti, Wisnu Siwi; Masfufah, Fitrianti Hidha; Hidayatulloh, Faisol (JoEMS (Journal of Education and Management Studies), 2024)
Mathematics is a very important branch of science and is often used in everyday life. However, there are still many students who still have difficulty learning this material. This research aims to develop a contextual-based E-module which aims to increase understanding of the concept of rectangular shapes in class VII students. The development method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. It is hoped that the results of the research can make a positive contribution in increasing understanding of the concept of rectangular shapes in class VII students. The product trial results show that the E-Module developed is valid and practical. This is shown by the results of media validation from mathematics lecturers which showed that 81% met the valid criteria. Validation of material from mathematics lecturers obtained 82% and mathematics teachers obtained 83% which met valid criteria, the practical value of the student response questionnaire was 62% and met practical criteria and the average student learning outcomes reached 85.625. So it can be concluded, this E-Module can support students' understanding of class 7 rectangular plane material and can be used to demonstrate students' understanding in learning.